2019
DOI: 10.1515/cclm-2019-0888
|View full text |Cite
|
Sign up to set email alerts
|

Two-center comparison of 10 fully-automated commercial procalcitonin (PCT) immunoassays

Abstract: Background This two-center study was designed to verify comparability of procalcitonin (PCT) values among 10 different commercial immunoassays. Methods A total number of 176 routine lithium-heparin plasma samples were divided in identical aliquots and simultaneously analyzed with 10 different PCT immunoassays, including Kryptor BRAHMS PCT sensitive, Abbott Architect BRAHMS PCT, Beckman Coulter Access PCT (on Access and DXI), BioMérieux Vidas BRAHMS PCT, Diasorin Liaison BRAHMS PCT, Fujirebio Lumipulse G BRAHM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Atellica IM 1600 could not be compared with other instruments because of a lack of published data. The Cobas e801 vs Kryptor comparison results are largely consistent with previous data [ 19 ]. Although Lippi, et al .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Atellica IM 1600 could not be compared with other instruments because of a lack of published data. The Cobas e801 vs Kryptor comparison results are largely consistent with previous data [ 19 ]. Although Lippi, et al .…”
supporting
confidence: 90%
“…[ 18 ] did not place a 5.00 μg/L limit on sample collection, they reported a similar correlation (ρ: 0.99; P <0.05) compared with our data; however, they reported a lower negative bias (slope: 0.89; y-intercept: –0.01; mean percentage difference: –14.9% [95% CI: –18.5 to –11.2%]) when comparing Cobas e801 with Kryptor. In addition, they obtained similar concordance results, with more discrepancies at the lower medical decision point of 0.25 μg/L than at 0.50 μg/L (96% at 0.25 μg/L and 99% at 0.50 μg/L) [ 19 ]. As all three immunoassays utilize the BRAHMS PCT monoclonal antibody, these discordances are likely to be related to the use of different calibrators by the manufacturers and/or lack of common reference materials, in addition to the innate differences in the immunoassay principles.…”
mentioning
confidence: 80%
“…PCT measurements should be done with high-sensitive PCT assays with sufficient precision in the relevant cut-off levels [51,52]. We recommend against the use of off-label assays with low quality because false-negative and false-positive PCT levels may affect treatment safety of patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, fixed budget for the lab in some hospitals limit broader PCT implementation as costs and savings occur in different departments. PCT testing often limited to -one to three tests per patient [5,6] Limitation for measurement by government Some countries restrict PCT reimbursement to certain indications and time points [31] Lack of high-quality (sensitive) POC technology For primary care and smaller emergency care institutions, POC devices may help to implement a PCT strategy Currently available POC tests often have insufficient technical performance and are not validated to be used for antibiotic stewardship [32] Educational support Educational material on PCT Many physicians have no formal education for the use of PCT and educational material is scarce [33] General ASP education and resources Lack of well-established infectious disease clinical training for hospital pharmacists, and the paucity of infectious disease specialists to oversee ASPs [34] Cultural differences Self-medication of patients with antibiotics In some countries, over-the-counter use of antibiotics may overrule physicians [26] Patient expectation for antibiotics Patients are demanding antibiotics for some conditions even if no bacterial infection is evident. Education of patients and relatives may be needed to make them understand the problems of antibiotic overuse have shown that for inpatient treatment in the ward and the ICU, measuring a baseline level within the first 24 h is helpful with repeated levels within 24-72 h depending on the clinical situation.…”
Section: Topic Comment Referencesmentioning
confidence: 99%
“…Some studies performed on the entire measurement range reported fine correlation with slopes ranging from 0.85 [ 14 ] to 1.1 [ 12 ] and a modest bias around 0.5 to 1 µg/L. More recently, Lippi et al [ 27 ] reported an acceptable correlation between Diazyme and BRAHMS PCT but with a large bias resulting in an overestimation reaching 38%. Our results are in agreement with this observation, the mean bias observed with Diazyme assay in the entire measurement range (up to 50 µg/L) reaching 4.69 µg/L.…”
Section: Discussionmentioning
confidence: 99%